Mathematical Creative Thinking Ability and Self-Regulation Character of Class X Students in Problem Based Learning assisted by Google Classroom in terms of Goal Orientation - Fattayati, Fattayati; Masrukan, Masrukan; Dwijanto, Dwijanto (Unnes Journal of Mathematics Education Research, 2021)
This research aims to find students' creative thinking skills by learning Problem Based Learning assisted by Google Classroom in terms of Goal Orientation. This research is a mixed method type of concurrent embedded design with a quasi-experimental quantitative research design. The research subjects were students of class X SMAN 1 Purwodadi Grobogan. The results obtained are that students with the mastery goal category can achieve the four indicators of mathematical creative thinking skills, namely fluency indicators, flexibility indicators, detail indicators, and authenticity indicators while students with performance goal categories can only meet two indicators of mathematical creative thinking ability. The indicators of flexibility and authenticity are not met. Students with the mastery goal category tend to have a high independence character, while students with the performance goal category tend to have moderate or even low independence characteristics.